A water-soluble photosensitive composite dry film and preparation method thereof
Through the combination of alumina and silica and the use of compatible agents, the problem of insufficient high-temperature resistance of photosensitive dry films at high temperatures is solved, and the mechanical strength and high-temperature resistance of the film material are significantly improved to form a denser film Body structure.
Patent Information
- Application Number
- CN202410890419.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-03
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-07-03
AI Technical Summary
The existing photosensitive dry films have insufficient high-temperature resistance and adhesion during long-term high-temperature operations, and the filler has poor fluidity in acrylic resin, making it difficult to form effective dispersion, which affects its high-temperature resistance.
Through the combination of alumina and silica, thermally stable organic groups are introduced, and compatibility is used to improve the dispersion and compatibility of the filler, and a water-soluble photosensitive composite dry film is prepared to enhance the mechanical strength and resistance of the film material. High temperature.
It significantly improves the mechanical strength and high temperature resistance of the film material, forms a denser film structure, improves the dispersion and compatibility of the filler, and enhances the thermal stability and adhesion of the material.
Smart Images

Figure BDA0004927327330000101 
Figure BDA0004927327330000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photosensitive dry films and relates to a water-soluble photosensitive composite dry film and a preparation method thereof. Background Art
[0002] Photosensitive dry film, also known as photoresist dry film, is a solid negative photoresist and one of the important raw materials for the production of printed circuit boards. In some scenarios that require long-term high-temperature operation, the photosensitive coating is often required to have high-temperature resistance and good adhesion. The conventional method is to add some specific high-temperature resistant fillers such as aluminum oxide, silicon nitride, and silicon dioxide to the coating, and select epoxy resin group prepolymers and other resins with good adhesion for photocuring. However, in acrylic resin, the use of too many epoxy groups alone is also not conducive to high-temperature yellowing resistance and aging resistance. When fillers are used to make up for their defects, the fillers have poor fluidity and are easy to agglomerate in acrylic resins, making it difficult to form an effective dispersion to improve high-temperature resistance. Summary of the invention
[0003] The purpose of the present invention is to provide a water-soluble photosensitive composite dry film and a preparation method thereof. The water-soluble photosensitive composite dry film prepared by the present invention is modified by compounding aluminum oxide and silicon dioxide, and while introducing more thermally stable organic groups, the dispersibility and compatibility of the filler in the system are increased by a compatibilizer, thereby significantly improving the mechanical strength and high temperature resistance of the film material.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A water-soluble photosensitive composite dry film comprises a substrate and a photosensitive layer arranged on the surface of the substrate, wherein the photosensitive layer comprises the following components in parts by weight: 50-60 parts of acrylic resin, 7-8 parts of functional filler, 15-20 parts of photosensitive monomer, 0.3-0.5 parts of photoinitiator, 0.2-0.4 parts of defoaming agent and 3-5 parts of deionized water.
[0006] As a preferred technical solution of the present invention, the substrate is selected from one or both of PET film and PE film; the photosensitive monomer is one or both of pentaerythritol triacrylate and (meth) lauryl acrylate; the photoinitiator is photoinitiator 651; and the defoamer is defoamer KS66.
[0007] As a preferred technical solution of the present invention, the preparation of the acrylic resin includes stirring and mixing methacrylic acid, butyl acrylate, methyl methacrylate, sodium dodecyl sulfate, aminopropyltrimethoxysilane and deionized water at a speed of 600-800 r / min for 1.0-1.5 hours, adding an initiator, heating and stirring at 85-90° C. for 1.5-2 hours to obtain the acrylic resin.
[0008] As a preferred technical solution of the present invention, in the preparation of acrylic resin, the mass ratio of methacrylic acid, butyl acrylate, methyl methacrylate, aminopropyltrimethoxysilane, initiator, sodium dodecyl sulfate and deionized water is 5-6: 5-6: 20-23: 4.0-4.3: 0.5-0.6: 1.0-1.3: 40-45; the initiator is initiator AIBA.
[0009] As a preferred technical solution of the present invention, the preparation method of the functional filler comprises the following steps:
[0010] Step 1: placing alumina, chitosan and deionized water in a reactor, mixing them, and then ultrasonically dispersing them, and freeze-drying them to obtain modified alumina;
[0011] Step 2: Mix silica, anhydrous ethanol and a coupling agent, perform ultrasonic oscillation, centrifuge, wash, and dry to constant weight to obtain modified silica;
[0012] Step 3: Mix the modified silica, anhydrous ethanol, a fluorine-containing compound and an initiator, heat and stir, centrifuge, wash, and dry to constant weight to obtain fluorine-modified silica;
[0013] Step 4: melt-extrude the modified alumina, fluorine-modified silica and the compatibilizer, and then granulate to obtain a functional filler.
[0014] As a preferred technical solution of the present invention, in step 1, the mass ratio of the aluminum oxide, chitosan and deionized water is 4-5:0.6-0.9:100; the ultrasonic dispersion is performed at a frequency of 300-400W for 10-15min.
[0015] As a preferred technical solution of the present invention, in step 2, the ultrasonic oscillation is oscillated at a power of 360W for 20-30min; the washing is performed by washing with anhydrous ethanol; the drying temperature is 80°C; the mass ratio of the silicon dioxide, anhydrous ethanol and coupling agent is 10-13:50-60:6.0-7.2; and the coupling agent is a silane coupling agent HD-105.
[0016] As a preferred technical solution of the present invention, in step three, the heating and stirring is stirring at a temperature of 35-40°C for 5-6h; the washing is washing with anhydrous ethanol; the drying temperature is 80°C; the mass ratio of the modified silica, anhydrous ethanol, fluorine-containing compound and initiator is 20-21:65-80:5-6:0.20-0.23; the fluorine-containing compound is one or more of 2-fluorocinnamaldehyde, 3-fluorocinnamaldehyde and 4-fluorocinnamaldehyde; and the initiator is ammonium cerium nitrate.
[0017] As a preferred technical solution of the present invention, in step four, the temperature of the melt extrusion is 180-190°C; the mass ratio of the modified alumina, fluorine-modified silica and the compatibilizer is 4.0-5.5:6.3-7.5:8-10; and the compatibilizer is styrene-glycidyl methacrylate copolymer.
[0018] A method for preparing a water-soluble photosensitive composite dry film comprises the following steps: acrylic resin, functional filler, photosensitive monomer, photoinitiator, defoamer and deionized water are weighed in parts by weight and mixed evenly, then coated on the surface of a substrate, and cured by ultraviolet irradiation to obtain the film.
[0019] Beneficial effects of the present invention:
[0020] The water-soluble photosensitive composite dry film prepared by the present invention is modified by compounding aluminum oxide and silicon dioxide, and while introducing more thermally stable organic groups, the dispersibility and compatibility of the filler in the system are increased by a compatibilizer, thereby significantly improving the mechanical strength and high temperature resistance of the film material. DETAILED DESCRIPTION
[0021] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0022] Example 1
[0023] A water-soluble photosensitive composite dry film, comprising a PET film substrate and a photosensitive layer arranged on the surface of the PET film substrate, wherein the photosensitive layer comprises the following components in parts by weight: 50 parts of acrylic resin, 7 parts of functional filler, 15 parts of photosensitive monomer, 0.3 parts of photoinitiator, 0.2 parts of defoamer and 3 parts of deionized water; the photosensitive monomer is a mixture of pentaerythritol triacrylate and (meth) lauryl acrylate in a mass ratio of 1:2; the photoinitiator is photoinitiator 651; the defoamer is defoamer KS66;
[0024] The preparation of the acrylic resin comprises the following steps: stirring and mixing methacrylic acid, butyl acrylate, methyl methacrylate, sodium dodecyl sulfate, aminopropyl trimethoxy silane and deionized water at a speed of 600 r / min for 1.0 h, adding an initiator, heating and stirring at 85° C. for 1.5 h, and obtaining the acrylic resin; in the preparation of the acrylic resin, the mass ratio of the methacrylic acid, butyl acrylate, methyl methacrylate, aminopropyl trimethoxy silane, initiator, sodium dodecyl sulfate and deionized water is 5:5:20:4.0:0.5:1.0:40; the initiator is initiator AIBA;
[0025] The preparation method of the functional filler comprises the following steps:
[0026] Step 1: placing alumina, chitosan and deionized water in a reaction kettle, mixing them, and then ultrasonically dispersing them, and freeze-drying them to obtain modified alumina; wherein the ultrasonic dispersion is performed at a frequency of 300W for 10 minutes; and the mass ratio of the alumina, chitosan and deionized water is 4:0.6:100;
[0027] Step 2: Mix silica, anhydrous ethanol and a coupling agent, perform ultrasonic oscillation, centrifuge, wash, and dry to constant weight to obtain modified silica; wherein the ultrasonic oscillation is oscillation at a power of 360 W for 20 minutes; the washing is washing with anhydrous ethanol; the drying temperature is 80° C.; the mass ratio of silica, anhydrous ethanol and coupling agent is 10:50:6.0; the coupling agent is silane coupling agent HD-105;
[0028] Step 3: Mix the modified silica, anhydrous ethanol, a fluorine-containing compound and an initiator, heat and stir, centrifuge, wash, and dry to constant weight to obtain fluorine-modified silica; wherein the heating and stirring is stirring at 35°C for 5 hours; the washing is washing with anhydrous ethanol; the drying temperature is 80°C; the mass ratio of the modified silica, anhydrous ethanol, fluorine-containing compound and initiator is 20:65:5:0.20; the fluorine-containing compound is 3-fluorocinnamaldehyde; and the initiator is ammonium cerium nitrate;
[0029] Step 4: melt-extrude the modified alumina, fluorine-modified silica and a compatibilizer, and then granulate to obtain a functional filler; wherein the temperature of the melt extrusion is 180° C.; the mass ratio of the modified alumina, fluorine-modified silica and the compatibilizer is 4.0:6.3:8; and the compatibilizer is styrene-glycidyl methacrylate copolymer;
[0030] A method for preparing a water-soluble photosensitive composite dry film comprises the following steps: weighing acrylic resin, functional filler, photosensitive monomer, photoinitiator, defoamer and deionized water in parts by weight and mixing them evenly to obtain a photosensitive composition, coating the composition on the surface of a PET film substrate, and curing the composition under 365nm ultraviolet irradiation to obtain a photosensitive composition.
[0031] Example 2
[0032] A water-soluble photosensitive composite dry film, comprising a PET film substrate and a photosensitive layer arranged on the surface of the PET film substrate, wherein the photosensitive layer comprises the following components in parts by weight: 53 parts of acrylic resin, 7.3 parts of functional filler, 17 parts of photosensitive monomer, 0.37 parts of photoinitiator, 0.27 parts of defoamer and 3.7 parts of deionized water; the photosensitive monomer is a mixture of pentaerythritol triacrylate and (meth) lauryl acrylate in a mass ratio of 1:2; the photoinitiator is photoinitiator 651; the defoamer is defoamer KS66;
[0033] The preparation of the acrylic resin comprises the following steps: stirring and mixing methacrylic acid, butyl acrylate, methyl methacrylate, sodium dodecyl sulfate, aminopropyl trimethoxy silane and deionized water at a speed of 667 r / min for 1.2 hours, adding an initiator, heating and stirring at 87° C. for 1.7 hours, and obtaining the acrylic resin; in the preparation of the acrylic resin, the mass ratio of methacrylic acid, butyl acrylate, methyl methacrylate, aminopropyl trimethoxy silane, initiator, sodium dodecyl sulfate and deionized water is 5.3:5.3:21:4.1:0.53:1.1:42; the initiator is initiator AIBA;
[0034] The preparation method of the functional filler comprises the following steps:
[0035] Step 1: placing alumina, chitosan and deionized water in a reactor, mixing them, and then performing ultrasonic dispersion, and freeze-drying to obtain modified alumina; wherein the ultrasonic dispersion is performed at a frequency of 333W for 12 minutes; the mass ratio of the alumina, chitosan and deionized water is 4.3:0.7:100;
[0036] Step 2: Mix silica, anhydrous ethanol and a coupling agent, perform ultrasonic oscillation, centrifuge, wash, and dry to constant weight to obtain modified silica; wherein the ultrasonic oscillation is oscillated at 360W power for 23 minutes; the washing is performed using anhydrous ethanol; the drying temperature is 80°C; the mass ratio of silica, anhydrous ethanol and coupling agent is 11:53:6.4; the coupling agent is silane coupling agent HD-105;
[0037] Step 3: Mix the modified silica, anhydrous ethanol, a fluorine-containing compound and an initiator, heat and stir, centrifuge, wash, and dry to constant weight to obtain fluorine-modified silica; wherein the heating and stirring is stirring at 37°C for 5.3h; the washing is washing with anhydrous ethanol; the drying temperature is 80°C; the mass ratio of the modified silica, anhydrous ethanol, fluorine-containing compound and initiator is 20.3:70:5.3:0.21; the fluorine-containing compound is 3-fluorocinnamaldehyde; and the initiator is ammonium cerium nitrate;
[0038] Step 4: melt-extrude the modified alumina, fluorine-modified silica and a compatibilizer, and then granulate to obtain a functional filler; wherein the temperature of the melt extrusion is 183° C.; the mass ratio of the modified alumina, fluorine-modified silica and the compatibilizer is 4.5:6.7:8.7; and the compatibilizer is styrene-glycidyl methacrylate copolymer;
[0039] A method for preparing a water-soluble photosensitive composite dry film comprises the following steps: weighing acrylic resin, functional filler, photosensitive monomer, photoinitiator, defoamer and deionized water in parts by weight and mixing them evenly to obtain a photosensitive composition, coating the composition on the surface of a PET film substrate, and curing the composition under 365nm ultraviolet irradiation to obtain a photosensitive composition.
[0040] Example 3
[0041] A water-soluble photosensitive composite dry film, comprising a PET film substrate and a photosensitive layer arranged on the surface of the PET film substrate, wherein the photosensitive layer comprises the following components in parts by weight: 57 parts of acrylic resin, 7.7 parts of functional filler, 18 parts of photosensitive monomer, 0.43 parts of photoinitiator, 0.33 parts of defoamer and 4.3 parts of deionized water; the photosensitive monomer is a mixture of pentaerythritol triacrylate and (meth) lauryl acrylate in a mass ratio of 1:2; the photoinitiator is photoinitiator 651; the defoamer is defoamer KS66;
[0042] The preparation of the acrylic resin comprises the following steps: stirring and mixing methacrylic acid, butyl acrylate, methyl methacrylate, sodium dodecyl sulfate, aminopropyl trimethoxy silane and deionized water at a speed of 733 r / min for 1.3 hours, adding an initiator, heating and stirring at 88° C. for 1.8 hours, and obtaining the acrylic resin; in the preparation of the acrylic resin, the mass ratio of methacrylic acid, butyl acrylate, methyl methacrylate, aminopropyl trimethoxy silane, initiator, sodium dodecyl sulfate and deionized water is 5.7:5.7:22:4.2:0.57:1.2:43; the initiator is initiator AIBA;
[0043] The preparation method of the functional filler comprises the following steps:
[0044] Step 1: placing alumina, chitosan and deionized water in a reaction kettle, mixing them, and then ultrasonically dispersing them, and freeze-drying them to obtain modified alumina; wherein the ultrasonic dispersion is performed at a frequency of 367W for 13 minutes; and the mass ratio of the alumina, chitosan and deionized water is 4.7:0.8:100;
[0045] Step 2: Mix silica, anhydrous ethanol and a coupling agent, perform ultrasonic oscillation, centrifuge, wash, and dry to constant weight to obtain modified silica; wherein the ultrasonic oscillation is oscillated at 360W power for 27 minutes; the washing is performed using anhydrous ethanol; the drying temperature is 80°C; the mass ratio of silica, anhydrous ethanol and coupling agent is 12:57:6.8; the coupling agent is silane coupling agent HD-105;
[0046] Step 3: Mix the modified silica, anhydrous ethanol, a fluorine-containing compound and an initiator, heat and stir, centrifuge, wash, and dry to constant weight to obtain fluorine-modified silica; wherein the heating and stirring is stirring at a temperature of 38°C for 5.7 hours; the washing is washing with anhydrous ethanol; the drying temperature is 80°C; the mass ratio of the modified silica, anhydrous ethanol, the fluorine-containing compound and the initiator is 20.7:75:5.7:0.22; the fluorine-containing compound is 3-fluorocinnamaldehyde; and the initiator is ammonium cerium nitrate;
[0047] Step 4: melt-extrude the modified alumina, fluorine-modified silica and a compatibilizer, and then granulate to obtain a functional filler; wherein the temperature of the melt extrusion is 187° C.; the mass ratio of the modified alumina, fluorine-modified silica and the compatibilizer is 5:7.1:9.3; and the compatibilizer is styrene-glycidyl methacrylate copolymer;
[0048] A method for preparing a water-soluble photosensitive composite dry film comprises the following steps: weighing acrylic resin, functional filler, photosensitive monomer, photoinitiator, defoamer and deionized water in parts by weight and mixing them evenly to obtain a photosensitive composition, coating the composition on the surface of a PET film substrate, and curing the composition under 365nm ultraviolet irradiation to obtain a photosensitive composition.
[0049] Example 4
[0050] A water-soluble photosensitive composite dry film, comprising a PET film substrate and a photosensitive layer arranged on the surface of the PET film substrate, wherein the photosensitive layer comprises the following components in parts by weight: 60 parts of acrylic resin, 8 parts of functional filler, 20 parts of photosensitive monomer, 0.5 parts of photoinitiator, 0.4 parts of defoamer and 5 parts of deionized water; the photosensitive monomer is a mixture of pentaerythritol triacrylate and (meth) lauryl acrylate in a mass ratio of 1:2; the photoinitiator is photoinitiator 651; the defoamer is defoamer KS66;
[0051] The preparation of the acrylic resin comprises the following steps: stirring and mixing methacrylic acid, butyl acrylate, methyl methacrylate, sodium dodecyl sulfate, aminopropyl trimethoxy silane and deionized water at a speed of 800 r / min for 1.5 hours, adding an initiator, heating and stirring at 90° C. for 2 hours, and obtaining the acrylic resin; in the preparation of the acrylic resin, the mass ratio of methacrylic acid, butyl acrylate, methyl methacrylate, aminopropyl trimethoxy silane, initiator, sodium dodecyl sulfate and deionized water is 6:6:23:4.3:0.6:1.3:45; the initiator is initiator AIBA;
[0052] The preparation method of the functional filler comprises the following steps:
[0053] Step 1: placing alumina, chitosan and deionized water in a reaction kettle, mixing them, and then ultrasonically dispersing them, and freeze-drying them to obtain modified alumina; wherein the ultrasonic dispersion is performed at a frequency of 400W for 15 minutes; and the mass ratio of the alumina, chitosan and deionized water is 5:0.9:100;
[0054] Step 2: Mix silica, anhydrous ethanol and a coupling agent, perform ultrasonic oscillation, centrifuge, wash, and dry to constant weight to obtain modified silica; wherein the ultrasonic oscillation is 360W for 30 minutes; the washing is performed with anhydrous ethanol; the drying temperature is 80°C; the mass ratio of silica, anhydrous ethanol and coupling agent is 13:60:7.2; the coupling agent is silane coupling agent HD-105;
[0055] Step 3: Mix the modified silica, anhydrous ethanol, a fluorine-containing compound and an initiator, heat and stir, centrifuge, wash, and dry to constant weight to obtain fluorine-modified silica; wherein the heating and stirring is stirring at 40°C for 6 hours; the washing is washing with anhydrous ethanol; the drying temperature is 80°C; the mass ratio of the modified silica, anhydrous ethanol, fluorine-containing compound and initiator is 21:80:6:0.23; the fluorine-containing compound is 3-fluorocinnamaldehyde; and the initiator is ammonium cerium nitrate;
[0056] Step 4: melt-extrude the modified alumina, fluorine-modified silica and a compatibilizer, and then granulate to obtain a functional filler; wherein the temperature of the melt extrusion is 190° C.; the mass ratio of the modified alumina, fluorine-modified silica and the compatibilizer is 5.5:7.5:10; and the compatibilizer is styrene-glycidyl methacrylate copolymer;
[0057] A method for preparing a water-soluble photosensitive composite dry film comprises the following steps: weighing acrylic resin, functional filler, photosensitive monomer, photoinitiator, defoamer and deionized water in parts by weight and mixing them evenly to obtain a photosensitive composition, coating the composition on the surface of a PET film substrate, and curing the composition under 365nm ultraviolet irradiation to obtain a photosensitive composition.
[0058] Comparative Example 1
[0059] Compared with Example 4, Comparative Example 1 is different in that silicon dioxide is used instead of aluminum oxide, and the other components, preparation steps and parameters are the same.
[0060] Comparative Example 2
[0061] Compared with Example 4, Comparative Example 2 is different in that alumina is used instead of silicon dioxide, and the other components, preparation steps and parameters are the same.
[0062] Comparative Example 3
[0063] Compared with Example 4, the difference in Comparative Example 3 is that chitosan is not used in step 1, and the other components, preparation steps and parameters are the same.
[0064] Comparative Example 4
[0065] Compared with Example 4, the difference of Comparative Example 4 is that no coupling agent is used in step 2, and the other components, preparation steps and parameters are the same.
[0066] Comparative Example 5
[0067] Compared with Example 4, Comparative Example 5 is different in that 3-fluorocinnamaldehyde is not used in step 3, and the other components, preparation steps and parameters are the same.
[0068] Comparative Example 6
[0069] Compared with Example 4, the difference in Comparative Example 6 is that no compatibilizer is used in step 4, and the other components, preparation steps and parameters are the same.
[0070] The photosensitive compositions prepared in Examples 1-4 and Comparative Examples 1-6 were tested as follows, and the test results are shown in Table 1.
[0071] Tensile strength test: The tensile properties of the cured film of the photosensitive composition were measured using a UTM5000 electronic universal testing machine. Samples with a size of 20 mm × 10 mm × 0.5 mm were used, and the crosshead speed was set to 10 mm / min. Each sample was measured three times, and the average value was calculated as the final result.
[0072] Hardness test: Test and rating are carried out in accordance with GB / T 6739-1996. The higher the rating number, the better the performance.
[0073] High temperature resistance test: The photosensitive compositions prepared in Examples 1-4 and Comparative Examples 1-6 were coated on a copper plate, cured by ultraviolet light to form a film, and then baked at 300° C. for 100 min, and the state of the film was observed.
[0074] Table 1
[0075]
[0076]
[0077] From the test results in Table 1, it can be seen that compared with Comparative Examples 1-6, the mechanical strength and thermal stability of the photosensitive composition prepared by the present invention are significantly better than those of Comparative Examples 1-6. The present invention fills the pore structure of alumina with silica to form a denser film structure, which can improve the mechanical strength of the film material. When chitosan is compounded with alumina, chitosan can enter the pore structure of alumina to form a network structure. During the melt extrusion process, the interaction between the aldehyde group on the fluorine-modified silica and the amino group of the modified alumina is used to form a Schiff base bond connection, while promoting the combination of silica and alumina. The epoxy group in the compatibilizer can react with the hydroxyl and carboxyl groups in the modified alumina and fluorine-modified silica, further increasing the binding force between the two and forming a denser structure. In addition, the styrene phase in the compatibilizer has good compatibility with the benzene ring structure of the fluorine-modified silica and the carbon-carbon unsaturated bond of the photosensitive composition system, which effectively promotes the dispersibility and compatibility of the functional filler in the system, thereby significantly improving the mechanical properties of the film material.
[0078] The present invention introduces silicon dioxide into alumina, and silicon dioxide can maintain the stable phase of alumina at a higher temperature, thereby improving the temperature resistance of the material. In addition, the doping of silicon dioxide can also change the pore structure of alumina, stabilize its oxygen lattice, and help improve the thermal stability of the material. In addition, the present invention modifies silicon dioxide through a coupling agent, introduces a thiol structure containing sulfur elements and chemically grafts it with fluorocinnamaldehyde, so that the fluorine element with corrosion resistance and high temperature resistance is introduced into the modified silicon dioxide, and then forms a Schiff base bond with self-repairing and high thermal stability with amino groups, thereby further improving the mechanical strength and high temperature resistance of the membrane material; the addition of a compatibilizer enables the functional filler to have good compatibility and dispersibility in the system, thereby further improving the mechanical properties and thermal stability of the material.
[0079] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A water-soluble photosensitive composite dry film, comprising a substrate and a photosensitive layer disposed on the surface of the substrate, characterized in that: The photosensitive layer comprises the following components by weight: 50-60 parts of acrylic resin, 7-8 parts of functional filler, 15-20 parts of photosensitive monomer, 0.3-0.5 parts of photoinitiator, 0.2-0.4 parts of defoamer and 3-5 parts of deionized water; Wherein, the preparation method of the functional filler comprises the following steps: Step 1: placing alumina, chitosan and deionized water in a reactor, mixing them, and then ultrasonically dispersing them, and freeze-drying them to obtain modified alumina; Step 2: Mix silica, anhydrous ethanol and a coupling agent, perform ultrasonic oscillation, centrifuge, wash, and dry to constant weight to obtain modified silica; the coupling agent is silane coupling agent HD-105; Step 3: Mixing the modified silica, anhydrous ethanol, a fluorine-containing compound and an initiator, heating and stirring, centrifuging, washing, and drying to constant weight to obtain fluorine-modified silica; the fluorine-containing compound is one or more of 2-fluorocinnamaldehyde, 3-fluorocinnamaldehyde and 4-fluorocinnamaldehyde; the initiator is ammonium cerium nitrate; Step 4: melt-extrude the modified alumina, fluorine-modified silica and a compatibilizer, and then granulate to obtain a functional filler; the compatibilizer is a styrene-glycidyl methacrylate copolymer.
2. The water-soluble photosensitive composite dry film according to claim 1, characterized in that: The photosensitive monomer is one or two of pentaerythritol triacrylate and (meth) lauryl acrylate; the photoinitiator is photoinitiator 651; the defoamer is defoamer KS66; and the substrate is one or two of PET film and PE film.
3. The water-soluble photosensitive composite dry film according to claim 1, characterized in that: The preparation of the acrylic resin comprises stirring and mixing methacrylic acid, butyl acrylate, methyl methacrylate, sodium dodecyl sulfate, aminopropyltrimethoxysilane and deionized water at a speed of 600-800 r / min for 1.0-1.5 hours, adding an initiator, heating and stirring at 85-90° C. for 1.5-2 hours, and obtaining the acrylic resin.
4. The water-soluble photosensitive composite dry film according to claim 3, characterized in that: In the preparation of acrylic resin, the mass ratio of methacrylic acid, butyl acrylate, methyl methacrylate, aminopropyltrimethoxysilane, initiator, sodium dodecyl sulfate and deionized water is 5-6: 5-6: 20-23: 4.0-4.3: 0.5-0.6: 1.0-1.3: 40-45; the initiator is initiator AIBA.
5. The water-soluble photosensitive composite dry film according to claim 1, characterized in that: In step 1, the mass ratio of the aluminum oxide, chitosan and deionized water is 4-5:0.6-0.9:100; and the ultrasonic dispersion is performed at a power of 300-400 W for 10-15 min.
6. The water-soluble photosensitive composite dry film according to claim 1, characterized in that: In step 2, the ultrasonic oscillation is oscillated at a power of 360W for 20-30min; the washing is performed using anhydrous ethanol; the drying temperature is 80°C; and the mass ratio of the silicon dioxide, anhydrous ethanol and coupling agent is 10-13:50-60:6.0-7.
2.
7. The water-soluble photosensitive composite dry film according to claim 1, characterized in that: In step three, the heating and stirring is stirring at a temperature of 35-40°C for 5-6 hours; the washing is washing with anhydrous ethanol; the drying temperature is 80°C; the mass ratio of the modified silica, anhydrous ethanol, fluorine-containing compound and initiator is 20-21:65-80:5-6:0.20-0.
23.
8. The water-soluble photosensitive composite dry film according to claim 1, characterized in that: In step 4, the temperature of the melt extrusion is 180-190° C.; the mass ratio of the modified alumina, fluorine-modified silica and compatibilizer is 4.0-5.5:6.3-7.5:8-10.
9. A method for preparing a water-soluble photosensitive composite dry film according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: acrylic resin, functional filler, photosensitive monomer, photoinitiator, defoamer and deionized water are weighed in parts by weight and mixed evenly, then coated on the surface of the substrate and cured to obtain the product.
